Controlled Fabrication of Bioactive Microtubes for Screening Anti-Tongue Squamous Cell Migration Drugs - Tang, Rongbing; Yang, Lu; Shen, Liheng; Ma, Xuan; Gao, Yinfeng; Liu, Yuan; Bai, Zhen; Wang, Xuemei (Frontiers in Chemistry, 2022)
The treatment of tongue squamous cell carcinoma (TSCC) faces challenges because TSCC has an aggressive biological behavior and manifests usually as widespread metastatic disease. Therefore, it is particularly important to screen out and develop drugs that inhibit tumor invasion and metastasis. The common non-steroidal anti-inflammatory drugs (NSAIDs), such as aspirin, shows anti-tumor effects including anti-migration. To screen out NSAIDs with excellent anti-migration effects for further clinical application, we made a hollow hydrogel microtube model prepared by the microfluidic devices. Based on the difference in liquid flow rate, TSCC cells (Cal27) were able to be evenly distributed in the hollow microtubes we engineered. Through the fluorescence microscope and laser scanning confocal microscope (LSCM), it was confirmed that the hollow hydrogel microtubes with specific dimensions was successfully constructed and the liquid velocity difference made cells arrange in order. Our microfluidic devices were cheap, and commercially available and can be assembled in a modular way, which are composed of a coaxial needle, silicone hose, and syringes. It has proved that the cells grow well in an artificial microtube with extracellular matrix (ECM) proteins by LSCM and flow cytometry. Periodic motility conferred a different motor state to the cells in the microtubes, more closely resembling the environment in vivo. The quantitative analysis of tumor cell migration could be achieved simply by determining the position of the cell in the microtube cross-section. We verified the anti-migration effects of three NSAIDs drugs (aspirin, indomethacin, and nimesulide) with artificial microtubes, obtaining the same results as conventional migration experiments. It is indicated that nimesulide showed great anti-migration potential in TSCC cells, among three NSAIDs. Our method holds great potential for application in the screening of anti-migration tumor drugs.